Right to counsel / Azhar Musa - Musa, Azhar (Faculty of Law, 1986)
The right to counsel was not an in,tended topic of my oroject paper until I came across an" interesting article by Ta"n Sri Mohammad Salleh bin Abbas. title "Riqht of an arrested person to consult counsel". When the project paper was imposed on every final year students. and upon spotting the article by Tan Sri Mohanvnad Salleh Abbas. it qive me the interest and idea to write on this topic with the intentio'n of hiqhliqhting the adequacy or otherwise of laws pertaining I Right to Counsell and also to see the extend and developments. problems as well as to look into various ways of over coming problems faced by the arrested person to consul this counsel.